2016
DOI: 10.1007/s40618-016-0432-x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D status in children and adolescents with autoimmune thyroiditis

Abstract: Low serum vitamin D is significantly associated with AIT in Egyptian children. However, vitamin D level is not an independent risk for the progression of AIT to overt hypothyroidism. BMI may have an influence on serum 25OHD levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 27 publications
1
29
0
1
Order By: Relevance
“…[6][7][8][9][10] Also, relation of vitamin D deficiency and autoimmune diseases including type 1 diabetes mellitus, systemic lupus erythematosus, autoimmune thyroiditis, and juvenile dermatomyositis has been researched in pediatric population. [12][13][14][15][16][17] Although there is lack of studies addressing role of vitamin D in pediatric AA, which is an autoimmune disease of the hair follicle, the relationship between vitamin D deficiency and AA in adult patients has been investigated. 6 Supporting our findings, it was reported in previous studies that topical or systemic administration of vitamin D analogs was detected as an effective agent in the progression of hair loss, and protective against the factors inducing hair loss.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…[6][7][8][9][10] Also, relation of vitamin D deficiency and autoimmune diseases including type 1 diabetes mellitus, systemic lupus erythematosus, autoimmune thyroiditis, and juvenile dermatomyositis has been researched in pediatric population. [12][13][14][15][16][17] Although there is lack of studies addressing role of vitamin D in pediatric AA, which is an autoimmune disease of the hair follicle, the relationship between vitamin D deficiency and AA in adult patients has been investigated. 6 Supporting our findings, it was reported in previous studies that topical or systemic administration of vitamin D analogs was detected as an effective agent in the progression of hair loss, and protective against the factors inducing hair loss.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, many studies have reported associations between vitamin D deficiency and a higher incidence of autoimmune disorders in adults such as RA, SLE, psoriasis, vitiligo, MS, IBD, and Behcet disease . Also, relation of vitamin D deficiency and autoimmune diseases including type 1 diabetes mellitus, systemic lupus erythematosus, autoimmune thyroiditis, and juvenile dermatomyositis has been researched in pediatric population …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, serum calcidiol correlated positively with FT4 levels. However, after adjustment for other potential confounding factors; age, sex and BMI, 25(OH)D 3 concentration was not an independent risk factor for the progression of subclinical to overt hypothyroidism (56).…”
Section: Hashimoto's Thyroiditismentioning
confidence: 82%